2020
DOI: 10.4314/gmj.v54i4s.4
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and clinical characteristics of the first cohort of COVID-19 recoveries at two national treatment centres in Accra, Ghana

Abstract: Introduction COVID-19 is a new disease, knowledge on the mode of transmission and clinical features are still evolving, new tests are being developed with inherent challenges regarding interpretation of tests results. There is generally, a gap in knowledge on the virus globally as the pandemic evolves and in Ghana, there is dearth of information and documentation on the clinical characteristics of the virus. With these in mind, we set out to profile the initial cohort of COVID-19 patients who recovered in Ghan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This is not surprising since these are some of the most commonly reported symptoms associated with COVID-19. 12 Quite surprisingly, between 52-90% of respondents indicated that shortness of breath/difficulty in breathing, sore throat, loss of smell and taste, fatigue/tiredness, diarrhoea and runny or stuffy nose were not symptoms of COVID-19. Another study reported that about 18% of participants had partial knowledge of COVID-19 symptoms, which is far lower than our findings.…”
Section: In Addition Objectivementioning
confidence: 98%
“…This is not surprising since these are some of the most commonly reported symptoms associated with COVID-19. 12 Quite surprisingly, between 52-90% of respondents indicated that shortness of breath/difficulty in breathing, sore throat, loss of smell and taste, fatigue/tiredness, diarrhoea and runny or stuffy nose were not symptoms of COVID-19. Another study reported that about 18% of participants had partial knowledge of COVID-19 symptoms, which is far lower than our findings.…”
Section: In Addition Objectivementioning
confidence: 98%